Controlling the optical properties of nanostructured oxide-based polymer films - Angastiniotis, Nicos; Christopoulos, Stavros; Petallidou, K C; Efstathiou, A. M.; Othonos, Andreas; Koutsokeras, Loukas E. (My University, 2021)
A bulk scale process is implemented for the production of nanostructured film composites comprising unary or multi-component metal oxide nanoparticles dispersed in a suitable polymer matrix. The as-received nanoparticles, namely Al[Formula: see text]O[Formula: see text], SiO[Formula: see text] and TiO[Formula: see text] and binary combinations, are treated following specific chemical and mechanical processes in order to be suspended at the optimal size and composition. Subsequently, a polymer extrusion technique is employed for the fabrication of each film, while the molten polymer is mixed with the treated metal oxide nanoparticles. Transmission and reflection measurements are performed in order to map the optical properties of the fabricated, nanostructured films in the UV, VIS and IR. The results substantiate the capability of the overall methodology to regulate the optical properties of the films depending on the type of nanoparticle formation which can be adjusted both in size and composition.
Keywords: Greenhouses; Microclimate; Natural Ventilation